Elucidation of Sequence–Function Relationships for an Improved Biobutanol In Vivo Biosensor in E. coli - Kim, Nancy M.; Sinnott, Riley W.; Rothschild, Lily N.; Sandoval, Nicholas R. (Frontiers in Bioengineering and Biotechnology, 2022)
Transcription factor (TF)-promoter pairs have been repurposed from native hosts to provide tools to measure intracellular biochemical production titer and dynamically control gene expression. Most often, native TF-promoter systems require rigorous screening to obtain desirable characteristics optimized for biotechnological applications. High throughput techniques may provide a rational and less labor-intensive strategy to engineer user-defined TF-promoter pairs using FACS and deep sequencing methods (sort-seq). Based on the designed promoter library’s distribution characteristics, we elucidate sequence-function interactions between the TF and DNA. In this work, we use the sort-seq method to study the sequence-function relationship of a 54-dependent, butanol-responsive TF-promoter pair, BmoR-PBMO derived from Thauera butanivorans, at the nucleotide level to improve biosensor characteristics, specifically an improved dynamic range. Activities of promoters from a mutagenized PBMO library were sorted based on gfp expression and subsequently deep sequenced to correlate site-specific sequences with changes in dynamic range. We identified site-specific mutations that increase the sensor output. Double mutant and a single mutant, CA(129,130)TC and G(205)A, in PBMO promoter increased dynamic ranges of 4-fold and 1.65-fold compared to the native system, respectively. In addition, sort-seq identified essential sites required for the proper function of the 54-dependent promoter biosensor in the context of the host.